Biology Education Students' Perceptions of the Benefits and Challenges of Cross-Department Lectures in the PMM Program at UMM - Adriani, Reski; Wahyuni, Sri; Asmah, Sitti (Jurnal Pendidikan Biologi, 2024)
Higher education in Indonesia is faced with various challenges in the era of globalization, which demands adaptation and innovation to produce graduates who are ready to compete at the global level. In response to this challenge, the Ministry of Education, Culture, Research and Technology introduced the Independent Student Exchange Program (PMM) within the Independent Campus initiative. This program allows students to study outside their home university for one semester, providing the opportunity to broaden their horizons, skills, and experiences. This research aims to explore Biology Education students' perceptions of the benefits and challenges they experience when taking cross-major courses at the University of Muhammadiyah Malang in the PMM program. The research method used was a qualitative descriptive approach with an open questionnaire instrument distributed to five PMM student participants. Research results show that students gain a variety of benefits from this program, including new perspectives, improved practical skills, diverse academic experiences, and expanded knowledge across disciplines. However, students also face various challenges, such as academic difficulties in understanding new material, differences in teaching methods, social and cultural adaptation, as well as technical and logistical obstacles. In conclusion, although PMM provides valuable learning experiences and enriches students' abilities, there is a need for better support to help them overcome the challenges they face. The results of this research can be a reference for improving the implementation of the PMM program in the future, so that it is more effective in supporting students' academic and personal development.